2005
DOI: 10.2174/1568010053622821
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Infections in the Pathogenesis of Autoimmune Diseases

Abstract: The autoimmune diseases result from inappropriate responses of the immune system to self antigens. The etiology of autoimmune diseases remains largely unknown but candidate etiologic factors include genetic abnormalities and infections. Although there are considerable data supporting the role of infections in a variety of autoimmune diseases, this role has been unequivocally established in only a few autoimmune diseases. The difficulty in establishing the infectious etiology of autoimmune diseases stems from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 66 publications
0
32
0
3
Order By: Relevance
“…One possible pathway recently proposed in the production of ANAs in SSc and other autoimmune diseases is molecular mimicry (48) in which persistent viral infection has been proposed as the causative event (49). Also Saito et al (50) have suggested that B cells link the production of autoantibodies and fibrosis in the Tsk1/ϩ mouse through a CD-19-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…One possible pathway recently proposed in the production of ANAs in SSc and other autoimmune diseases is molecular mimicry (48) in which persistent viral infection has been proposed as the causative event (49). Also Saito et al (50) have suggested that B cells link the production of autoantibodies and fibrosis in the Tsk1/ϩ mouse through a CD-19-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Various infectious micro organisms such as bacteria, viruses, helminthes and fungi are associated with vasculitic syndromes. While staph aureus infections have already been linked to Wegener's granulomatosis (Popa et al 2002;Popa et al 2003) and Henoch-Schonlein purpura (Eftychiou et al 2006;Samarkos and Vaiopoulos, 2005) coagulase negative staph to the best of our knowledge had only once been reported to cause a cutaneous small vessel vasculitis (Cantwell and Kelso, 1982) in a severely immunocompromised patient.…”
Section: Discussionmentioning
confidence: 96%
“…A chronic form of this illness may present with progressive symptoms and result in chronic infl ammatory demyelinating polyneuropathy (CIDP) [7,8]. GBS is usually a post-infectious disorder occurring outside the context of pre-existing disease, and represents a model for post-infectious autoimmune disorders [9]. The criteria for a diagnosis of GBS are summarized on clinical features, lumbar puncture, nerve conduction studies, magnetic resonance imaging, and serum antibodies [10].…”
Section: Introductionmentioning
confidence: 99%